KEMUNCULAN ACAK PRONOMINA PERTAMA TUNGGAL DALAM BUKU SASTRAWAN BERKARYA: KAJIAN LINGUISTIK KORPUS - Yunanfathur Rahman; Lutfi Saksono; Ajeng Dianing Kartika (Universitas Negeri Surabaya, 2023)
This article describes the use of quantitative data processing using the Chi-Square Test (X2) analytical statistical technique, which is applied to linguistic problems related to the relationship between first singular pronouns and the data corpus. Based on a corpus of data collected from the website of Badan Bahasa in the form of books by 18 writers in 2016, 2017 and 2018, this article measures the relationship between singular first person pronouns AKU and SAYA to a data corpus. Chi-Square test (X2) determines the relationship between these two variables (namely AKU and SAYA) to the data corpus. The results of the analysis show that there is an association pattern that cannot be said to be statistically random between the appearance or absence of the pronouns AKU and SAYA in the existing corpus. With quantitative analysis like the one shown in this study, the association pattern of apparently random variants can finally be statistically proven as well. The existence of a statistically significant distribution raises the possibility of linguistically interesting things to be investigated further.